Understanding The Concept Of Servant Leadership In The Digital Age Through Keywords Mapping - Kansil, Marlon Semuel Contantin; Sujuti, Andi Fanny (UI Scholars Hub, 2024)
The contemporary digital age has ushered in profound transformations in various facets of leadership. This paper endeavours to conduct a comprehensive literature analysis aimed at elucidating the enduring relevance and adaptability of the concept of Servant Leadership within the dynamic landscape of the digital era. The study commences by establishing the foundational principles of Servant Leadership, grounded in empathy, altruism, and a commitment to community stewardship. These principles are explored through an examination of seminal works by Greenleaf and subsequent scholarship. The digital age, characterized by technological advancements and virtual workspaces, presents distinctive challenges and opportunities for leadership paradigms. As such, this paper scrutinizes the application of Servant Leadership principles in digital leadership contexts. It delves into the challenges of maintaining personal connections and empathy in digital interactions, the balance between technology and compassionate leadership, and the imperative of fostering a culture of continuous learning and adaptability. Furthermore, the paper appraises the existing body of literature pertaining to the compatibility of Servant Leadership with the demands of the digital age. The synthesis of these insights offers a nuanced perspective on the applicability of Servant Leadership in the digital age, shedding light on the need for leaders to adapt and innovate while adhering to the core principles of innovation, empathy, motivation, privacy, and ethical stewardship. In conclusion, this literature analysis underscores the enduring value of Servant Leadership as it traverses the complex terrain of the digital era, advocating for its continued relevance and adaptation to contemporary leadership challenges.